The moral skeptic - Superson, Anita M. (Oxford : Oxford University Press, 2009)
Anita Superson challenges the traditional picture of the skeptic who asks, 'Why be moral?'. While holding that the skeptic's position is important, she builds an argument against it by understanding it more deeply, and then shows what it would take to successfully defeat it.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Ethics; Skepticism